The impact of biomass power plants on Brazilian workers' income: a synthetic difference-in-differences approach - Daniel de Abreu Pereira Uhr; Mikael Jhordan Lacerda Cordeiro; Júlia Gallego Ziero Uhr (EconomiA, 2024)
Purpose: This research assesses the economic impact of biomass plant installations on Brazilian municipalities, focusing on (1) labor income, (2) sectoral labor income and (3) income inequality. Design/methodology/approach: Municipal data from the Annual Social Information Report, the National Electric Energy Agency and the National Institute of Meteorology spanning 2002 to 2020 are utilized. The Synthetic Difference-in-Differences methodology is employed for empirical analysis, and robustness checks are conducted using the Doubly Robust Difference in Differences and the Double/Debiased Machine Learning methods. Findings: The findings reveal that biomass plant installations lead to an average annual increase of approximately R688.00 in formal workers' wages and reduce formal income inequality, with notable benefits observed for workers in the industry and agriculture sectors. The robustness tests support and validate the primary results, highlighting the positive implications of renewable energy integration on economic development in the studied municipalities. Originality/value: This article represents a groundbreaking contribution to the existing literature as it pioneers the identification of the impact of biomass plant installation on formal employment income and local economic development in Brazil. To the best of our knowledge, this study is the first to uncover such effects. Moreover, the authors comprehensively examine sectoral implications and formal income inequality.
Keywords: C21; O13; Q42; 330; Biomass power plants; Brazilian workers; Income